Research in Service-Oriented Architecture with Cloud and SaaS Solutions - G, Marimuthu (International Journal of Computer Sciences and Engineering, 2019)
The Software as a Service (SaaS) and Service Oriented Architecture (SOA) leads the confusion which one an apt for the nowadays. SaaS cloud delivery model becomes popular. So, the clear understanding is necessary to know the concepts of the SaaS delivery model and SOA architecture. In this paper is used to explore the concepts of SaaS and SOA to give a better understanding of these two technologies.